Unmanned aerial vehicle for fire surveillance and monitoring - Á. Madridano; S. Campos; A. Al-Kaff; F. García; D. Martín; A. Escalera (Revista Iberoamericana de Automática e Informática Industrial RIAI, 2020)
Forest fires continue to be one of the major environmental problems facing society today. In addition to the high environmental impact, the destruction of ecosystems and possible human losses, the economic costs of fire-fighting must be added. All these reasons have led to the search, in current technology, for tools and systems to help in fire-fighting tasks and, more specifically, the use of Unmanned Aerial Vehicles (UAVs). The fact that UAVs can reach remote locations quickly and embark on sensors and devices to assist in dangerous and risky tasks makes them ideal for firefighting. This work includes the development, in collaboration with Telefónica Digital España, of an effective tool using current technology present in robotics, in which a drone is capable of carrying out fire surveillance and monitoring tasks autonomously, thanks to the sensors and devices on board. In addition, a graphical interface is implemented that allows the exchange of information between the aircraft and the ground user.